2014
DOI: 10.1123/jsep.2013-0249
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Fatigue Effects on Physical Performance During Running

Abstract: This study investigated the effect of cognitive fatigue on physical performance in a paced running task. Experienced runners (n = 20) performed two 3,000-m runs on an indoor track, once after cognitive fatigue, and once under nonfatigued conditions. Completion times were significantly slower in the cognitive fatigue condition (M = 12:11,88 min, SD = 0:54,26), compared with the control condition (M = 11:58,56 min, SD = 0:48,39), F(1, 19) = 8.58, p = .009, eta2p = .31. There were no differences in heart rate, t(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
90
4
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 9 publications
20
90
4
4
Order By: Relevance
“…This suggests that individuals did not gain any knowledge due to reading the information from Mind (2011). Firstly, due to the lengthy and repetitive questionnaire provided to participants, this may have contributed to cognitive fatigue (MACMAHON et al 2014), consequently individuals may have randomly selected their answers, resulting in a lower knowledge score being calculated.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that individuals did not gain any knowledge due to reading the information from Mind (2011). Firstly, due to the lengthy and repetitive questionnaire provided to participants, this may have contributed to cognitive fatigue (MACMAHON et al 2014), consequently individuals may have randomly selected their answers, resulting in a lower knowledge score being calculated.…”
Section: Discussionmentioning
confidence: 99%
“…the hypothesis that mental fatigue caused negative effects on tactical action quality and intensity in the distance covered by players was confirmed. Studies show that mental fatigue impairs physical performance in such sports as running [25], cycling [26], and cricket [27], as well as in soccer physical tests [10,14]. Although the results indicated an increase in the distance covered in speeds corresponding to zone 3 (10-12.9 km/h) and in higher intensity zones ( 18 km/h), we understand that covering greater distances in elevated speeds as a consequence of poor tactical actions can negatively influence soccer players' performance.…”
Section: Discussionmentioning
confidence: 99%
“…It was conjectured that if a participant was unaccustomed to a certain condition or did not believe in its usefulness that it may have a negative effect on performance. Past studies have shown that what participants do prior to performance, in addition to their perceptions of recovery, can exert an effect on performance [19,21,22]. Some of the mechanisms that may modulate these effects include reduction of anxiety and increased selfbelief [20].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from dehydration-related fatigue, which has been firmly established [11,12], other proposed possible mechanisms focus on fluctuations in glycogen, creatine phosphate (CP), potassium, and blood lactate, but the findings have been conflicting and no single factor has been definitively linked to fatigue [5,[13][14][15][16][17][18]. There has also been increasing support for the role of the CNS and psychological factors such as motivation, experience, routines, self-belief, and perception of exertion/recovery [19][20][21][22]. While their true significance remains controversial, successful recovery would seemingly involve restoring some combination of these variables.…”
Section: Introductionmentioning
confidence: 99%